Effect of the molecular weight on the physicochemical properties of poly(lactic acid) nanoparticles and on the amount of ovalbumin adsorption (2011)
ABSTRACT: Nanopartículas de poli(ácido lactico) (PLA) foram preparadas para serem usadas como plataformas potenciais em sistemas de vacinas. PLA comercial de elevado peso molecular (PLAHMW) com Mw 1,5 × 105 e PLA de baixo peso molecular (PLALMW) com Mw 9,3 × 103 foram obtidos por policondensação direta a partir de D,L ácido lático e usados para preparar nanopartículas pelo método de deslocamento de solvente. O efeito do peso molecular nas propriedades físico-químicas dos polímeros, nas dispersões das nanopartículas e na quantidade de adsorção de ovalbumina (OVA) foi estudado. PLAHMW e PLALMW foram caracterizadas por espectroscopia de infravermelho com transformada de Fourier (FTIR), análise termogravimétrica (TGA), calorimetria diferencial de varredura de temperatura modulada (MTDSC) e cromatografia de permeação de gel (GPC). A distribuição do tamanho das partículas e potencial-ζ das dispersões obtidas foram medidas por espalhamento de luz dinâmico (DLS) e espectroscopia eletroacústica, respectivamente. A adsorção de ovalbumina em nanopartículas foi avaliada pelo método de Bradford. A dispersão de PLALMW mostrou menores valores de potencial-ζ e tamanhos maiores comparados à dispersão de PLAHMW. Uma menor adsorção de OVA foi alcançada por PLA LMW. Poly(lactic acid) (PLA) nanoparticles were prepared to be used as potential platform for vaccine systems. Commercial high molecular weight PLA (PLAHMW) with Mw 1.5 × 105 and low molecular weight poly(lactic acid) (PLALMW) with Mw 9.3 × 103 were obtained by direct polycondensation from D,L lactic acid and used to prepare nanoparticles by solvent displacement method. The effect of the molecular weight on the physicochemical properties of the polymers, on the nanoparticles dispersions and the amount of ovalbumin (OVA) adsorption was studied. The PLAHMW and PLALMW were characterized by Fourier transformed infrared spectroscopy (FTIR), thermogravimetrical analysis (TGA), modulated temperature differential scanning calorimetry (MTDSC) and gel permeation chromatography (GPC). The particle size distribution and ζ-potential of the obtained dispersions were measured by dynamic light scattering (DLS) and electroacoustic spectroscopy, respectively. The ovalbumin adsorption on nanoparticles was evaluated by the Bradford method. PLALMW dispersion showed lower ζ-potential values and larger sizes compared to PLAHMW dispersion. A minor OVA adsorption was achieved for PLALMW.